Optimalisasi Pupuk Cair Urin Sapi sebagai Exogenous Growth Factor Tanaman Bawang Merah - As'ad Syamsul Arifin; Permata Ika Hidayati (IKIP Budi Utomo Malang, 2022)
This study aims to determine the optimization of cow urine liquid fertilizer on the growth of shallots (Allium ascalonicum L.). The research method used was an experiment using a completely randomized design (CRD), consisting of 5 treatments and 4 replications, namely treatment A (0 ml cow urine/polybag), treatment B (50 ml cow urine/polybag), treatment C (100 ml cow urine/polybag), treatment D (150 cow urine/polybag), treatment E (200 ml/l cow urine/polybag). Observations were made on shallot plant height, tuber wet west, number of bulbs, and tuber diameter. The results of the study, p<0,01 and p<0.05 on the calculation of wet weight and number of bulbs, as well as on the diameter of shallot bulbs so that the application of cow urine liquid fertilizer can affect the optimization of shallot plant height.